Professional Training for Engineering Teachers - Wakhlu, O. N. (Journal of Engineering Education Transformations, 1994)
The paper examines the need for professional training for engineering teachers towards more creative and wholesome learning process in the technical institutions. A preliminary approach to course design for professional training has been discussed . This could form a basis of discussion within the profession. In particular, feedback from teachers in practice would be very helpful in determining the contents, duration and modus operandi for the training programme finally adopted.